ERRORS FOUND ON THE ENGLISH TRANSLATION SENTENCES OF THE THIRD-YEAR STUDENTS OF ENGLISH AT IKIP BUDI UTOMO - Enis Fitriani (Journey: Journal of English Language and Pedagogy, 2020)
This study aimed to describe and classify the grammatical errors found on English translation sentences in terms of syntax and morphology. The analysis procedure applied was based on the surface strategy taxonomy proposed by Dulay et al. in which errors were categorized into errors of: omission, addition, misformation, and misordering. The result of this study indicated that the highest frequency is errors of misformation which covers 58 errors (46%), followed by omission which covers 47 errors (27%), addition with 12 errors (10%), and the lowest is misordering, 9 errors (7%). In terms of syntax and morphology, the researcher found 17 errors (18%) in articles, 7 errors (7%) in pronouns, 21 errors (22%) in prepositions, 15 errors (16%) in inflectional endings, 26 errors (28%) in tenses, and 8 errors (9%) in derivational endings. Thus, errors in tenses are the highest frequency of errors, and, errors in derivational morphemes are the lowest.